A terapia comunitária como instrumento de ação profissional do assistente social: uma análise à luz de Michel Foucault - Pagano, Thaís (2011)
In this research it is analyzed the way on how the social worker s professional practice is processed while community therapist, and how it establishes a parallel with the power relations in Michel Foucault, starting from the idea that this relation is possible from the conception of Community Therapy as a place to perform a counter-discourse and resistance, pointing this way a possibility of professional performance that transcends the role of the intellectual and of the expert, in foucaultian s terms. The present study attempts to understand if it is possible to think the social worker s practice, while community therapist, within the ethicalpolitical project of the profession through the idea of freedom, in order to locate a professional practice, guided by the use of knowledge-power so that it allows thinking on the resistance within the social worker and has found itself committed to knowledge through the exercise of questioning and reflection. From the author s work as a social worker in the area of public health, the process that orients this research is due through the comprehension of the movement for the democratization of public health across the country, as well as the challenges put to healthcare professionals; by the reflection on the work of the Social Service on the Health Center I Vila Mariana; the evaluation from the foucaultian analysis of the relations of power and understanding of the path of the construction of Community Therapy (CT) and its action proposals. Readings were made from the testimonies of participants of the CT at the Health Center I Vila Mariana, seeking to understand the impact of this practice on subject s lives. The evaluation of reports of experiences with the CT through the country, made by community therapists, healthcare professionals as well as a debate and interview with some community therapists, from different professional formation and related to other institutions, had the objective to share experiences and different perspectives, in order to identify whether it is possible through this practice, the part of the social worker as a community therapist, to establish a horizontal relationship with the group members. The trajectory performed in this work showed that CT can be an instrument of the Social Worker if incorporated in a critical way, through an investigative approach, committed to the emancipation of the subject, by offering a space of listening and knowledge of the everyday life of the people